2016
DOI: 10.1002/cae.21715
|View full text |Cite
|
Sign up to set email alerts
|

Construction and evaluation of PHP‐based management and training system for electrical power laboratory

Abstract: ABSTRACT:The online management and training of information for laboratories has rarely been discussed in the traditional education system design. However, it plays a vital role in informatization and automation of electrical power laboratory. Using PHP: Hypertext Preprocessor (PHP), we have designed and developed an online management and training environment targeted for electrical power laboratory. In this article, the Model-ViewController (MVC) architecture cooperative designed for the management and trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Literature [6] rarely discusses online management and training of laboratory information in traditional educational system design. An online management and training environment for power laboratories was designed and developed using a hypertext preprocessor, and an empirical analysis confirmed that a management and training system for power laboratories can lead to better learning interests and outcomes.…”
Section: Related Researchmentioning
confidence: 99%
“…Literature [6] rarely discusses online management and training of laboratory information in traditional educational system design. An online management and training environment for power laboratories was designed and developed using a hypertext preprocessor, and an empirical analysis confirmed that a management and training system for power laboratories can lead to better learning interests and outcomes.…”
Section: Related Researchmentioning
confidence: 99%
“…Its database was constructed by Microsoft Access, whose security is poor and has a lack of performance when dealing with a large amount of data. Yu et al developed a PHP‐based management and training system for electrical power laboratory. It was mentioned that that system lacked for data processing, and its main work of future was for the experiment data post‐processing, which has fulfilled in the WathyLab system.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, we find numerous applications of computer‐assisted teaching (through simulation etc.) in elucidating and complimenting theoretical concepts , design based problem‐solving , laboratory experiments [7,8] to quote a few, in practically all engineering disciplines, and management as well.…”
Section: Introductionmentioning
confidence: 99%